Quality Control Patient Trigger Ventilator using Negative Air Pressure - Rahman Maulana Jundika; Ardy Seto Priambodo (Journal of Robotics, Automation, and Electronics Engineering, 2023)
This research aims to develop a quality control tool for patient trigger ventilators at PT Stechoq Robotika Indonesia. The increasing demand for ventilators has driven PT Stechoq Robotika Indonesia to create high-end ventilators. However, the production process faces challenges, particularly in the manual quality control of patient trigger alarms. Therefore, an automated quality control tool is needed to replace the manual mechanism. The research utilizes the Research and Development method. Trials are conducted on SIMV and CPAP modes with variations in pressure trigger and flow trigger parameters to evaluate the performance of patient trigger alarms on ventilators. The results of implementing the patient trigger quality control tool show an average accuracy rate of 70% for pressure and flow triggers in SIMV and CPAP modes. This tool is expected to reduce time and effort in the quality control process while improving the accuracy of triggering patient alarms on ventilators. Overall, the patient trigger ventilator quality control tool has significant potential in the ventilator industry, with positive implications for product quality and production efficiency at PT Stechoq Robotika Indonesia.